Ability of endophytic fungi isolated from Nepenthes ampullaria to degrade polyurethane - Aazani, Mujahid; Müller, Moritz; Bong, Shirley Wuan Lii; Changi, Wong; Al-Obaidi, Jameel R.; Norasfaliza, Rahmad (Malaysian Society for Microbiology, 2017)
Aims: Waste electric and electronic equipment (WEEE) are among the fastest growing waste products worldwide and solutions to their remediation are urgently needed. Bioremediation is a green approach that is helpful to minimize environmental pollution associated with Electronic waste (E-waste). The present study aimed at exploring the potential of endophytic fungi from Nepenthes ampullaria for bioremediation purposes of the plastic component in E-waste, polyurethane (PUR) polymers. Methodology and results: Endophytic fungal isolates were assessed for their ability to degrade PUR as well as their ability to utilise PUR as sole carbon source. Nine (9) out of 150 isolates demonstrated the ability to efficiently degrade polyurethane in solid medium and the top three (3) isolates were able to grow on PUR as the only carbon source. These three isolates were identified using ITS1 and ITS4 and found to be closely related to the genus Pestalotiopsis. The top two of the three isolates were then assessed for their esterase enzyme activity as well as changes in their proteome when grown with and without PUR. The highest enzymatic activity was found to be 1850.4 U/mL when tested using pnitrophenol acetate as the substrate. Analyses of the 2-dimensional electrophoresis profile revealed changes in the abundance of proteins when treated with polyurethane. Conclusion, significance and impact of study: This study is to our knowledge the first on endophytes isolated from N. ampullaria that can degrade PUR, and also their proteomes. Results obtained from this study can in the future help to reduce polyurethane wastes. Besides degrading PUR polymer, endophytic fungi produce potential valuable proteins that may find broad applications in bioremediation applications.